DETEKSI PIPA GAS DALAM TANAH MENGGUNAKAN METODE GROUND PENETRATING RADAR - CAESAR PASARIBU, ALBERT
Ground Penetrating Radar (GPR) or commonly reffered as Georadar is a non-destructive geophysical survey method using high-frequency electromagnetic waves. GPR method is used for subsurface imaging process or detecting the presence of objects in the ground. When the electromagnetic waves propagate, it will be transmitted and reflected uniquely due to various elements under the ground that has different dielectric constant, thus providing unique patern of response (radargram) were recorded. GPR method is now widely used in many fields, such as archeology, geology, geotechnics, and forensics . In this final project GPR method is used to do the detection of a gas pipeline in the ground along the river Cikarang Bekasi Laut (CBL). The obtained datas are processed using MatlabGPR program to apply filters and corrections to achive the optimal interpretation of pipeline position.